Analisis Potensi Kawasan Ekowisata Dalam Meningkatkan Pendapatan Asli Daerah (PAD) Di Pulau Maitara Kota Tidore Kepulauan - Saifuddin, Abdullah (Bongaya Journal of Research in Accounting (BJRA), 2024)
This study is a quantitative research that aims to examine the influence of tourist attractions (X1), Number of Visitors (X2), lodging rental costs (X3) on the original income of the PAD (Y) region in this study using a data collection method by distributing questionnaires, interviews and documentation, the population in this study is Maitara island tourist objects and 60 people consisting of visitors to tourist attractions, The surrounding community and culinary sellers around the tourist object are the samples in this study, which uses the purposive sampling technique in collecting samples. The analysis tool used is the application of SPSS 23, a statistical test tool. The results showed that the variables of the coefficient of tourism objects had a positive value with a significant level 0,001<0,05, so that Ho accepted means tourist object (X1) has a significant effect on Regional Original Revenue (Y), The Number of Visitors coefficient has a positive value with a significant level 0,001< 0,05, so that Ho accepted means the number of visitors (X2) has a significant effect on Regional Original Revenue (Y), and the coefficient of Lodging rental costs at a significant level 0,020 > 0,05, so that Ho ditolak means the cost of lodging rent (X3) does not have a significant effect on Regional Original Revenue (Y), Thus the hypothesis is rejected.